Do discutir e resolver em matemática : reflexões sobre a constituição de um grupo de estudos entre educadores matemáticos - De Paula, Enio Freire (2009)
The present text discuss the proposal of creation and development in a study group of mathematicians, named GEDMAT, turned to the Mathematics teachers from the public schools and students from a Mathematics teaching course of a privet university, whose main aim is to provoke reflexions related to the Mathematics activities based in the Group Work about the Problems Resolution. The proposed work characterized as a cooperative research, of quantitative interpretative mark, whose objective was to investigate the impact on the acting and under graduation teachers' pedagogical practices, of its participation in a study group with cooperative characteristics formed for this intention. The research characterizes as cooperative, whereas though the members of the group formed have put themselves available to the researcher, the investigative problem conception, the conclusions and the final written are exclusivities of this and not of the group. When we analyse the gotten materials with the research activity, we conclude that this work acted as a professional developing process involved in this activity, giving qualitative improvements, in special to the familiarization with a possibility of a teaching strategy accorded in the teachers' debates and also among the teachers and the students.